KANDUNGAN ZAT GIZI MAKRO DAN VITAMIN PRODUK BUAH PEDADA (SONNERATIA CASEOLARIS) - Ruth Dwi Elsa Manalu; Ella Salamah; Fifi Retiaty; Nia Kurniawati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2013)
ABSTRACT Mangrove (Sonneratia caseolaris) grows in brackish waters.Its fruits, pedada, contains beneficial vitamin and has not been processed to jam and syrup. This study was aimed to determine the composition of macro nutrient and vitamin A, B1, B2, C of pedada and its products. Design of the study was complete randomized design of two replications. The results showed that proximate composition based on dried basis was 9.2 percent protein, 4.8 percent fat, and 77.6 percent carbohydrate. Macronutrient content of jam and syrup was lower than that of fresh fruit, except for carbohydrate. Vitamin A content in 100 g of pedada was 11.21 (RE) and in jam and syrup was 1.27 (RE) and 0.64 (RE) respectively. Vitamin B1 content in 100 g of fresh pedada was 5.04 mg, while in jam and syrup were 4.2 mg and 6.72 mg, respectively. Vitamin B2 content in 100 g of fresh pedada was 7.65 mg, while in jam and syrup were 1.94 mg and 1.12 mg, respectively. Vitamin C content in 100 g of fresh pedada was 56.74 mg and decreased to 12.20 mg and 17.08 mg in jam and syrup, respectively. Pedada and its products could contribute as source of macro and micro nutrient in the diet of community. Keywords: pedada (sonneratia caseolaris), pedada’s jam, pedada’s syrup, vitamin ABSTRAK Mangrove (Sonneratia caseolaris) tumbuh di perairan payau. Buahnya, pedada, mengandung vitamin, dan belum pernah diolah menjadi selai dan sirup. Penelitian ini bertujuan menentukan komposisi zat gizi makro dan potensi vitamin A, B1, B2, C dalam buah pedada dan produk olahannya. Desain penelitian adalah rancangan acak lengkap dengan dua ulangan. Hasil penelitian menunjukkan bahwa komposisi proksimat buah pedada segar berdasarkan bobot kering adalah 9,2 persen protein, 4,8 persen lemak, dan 77,6 persen karbohidrat. Kandungan zat gizi makro pada produk selai dan sirup lebih rendah, sedangkan kandungan karbohidratnya lebih tinggi. Kandungan vitamin A dalam 100 g pedada segar sebesar 11,21 (RE) dan setelah diolah menjadi selai dan sirup, menjadi 1,27 (RE) dan 0,64 (RE). Vitamin B1 dalam 100 g pedada segar adalah 5,04 mg/100g, pada selai 4,2 mg, dan pada sirup 6,72 mg. Vitamin B2 dalam 100 g pedada segar sebesar 7,65 mg, pada selai 1,94 mg dan sirup 1,12 mg. Vitamin C dalam 100 g pedada segar sebesar 56,74 mgdan menurun menjadi 12,20 mg dan 17,08 mg masing-masing pada selai dan sirup. Pedada dan produk olahannya berupa selai dan sirup dapat memberikan asupan zat gizi makro maupun mikro pada makanan masyarakat. [Penel Gizi Makan 2013, 36(2): 135-140] Kata kunci: pedada (Sonneratia caseolaris), selai pedada, sirup pedada, vitamin